Protein engineering and other bio-synthetic routes for bio-based materials: Current uses and potential applications - Carissa M. Soto (Frontiers Research Topics, 2015)
In the past 20 years protein engineering has been used for the production of proteins mostly for biological applications. The incorporation of artificial amino acids and chemical handles into proteins had made possible the design and production of protein-based materials like hybrid inorganic-organic materials, smart/ responsive materials, monodisperse polymers, and nanoscale assemblies. In the current topic, we cover current uses and envision future applications of materials generated using protein engineering and biosynthesis techniques.